(untitled) (Brazilian Journal of Health Research, 2025)
Introduction: Nasal cavities, paranasal sinuses and skull base tumors are rare and usually aggressive lesions. The clinic is generally nonspecific and insidious, tending to lead these patients to a poor prognosis. In diagnosis and surgical planning, biopsy and imaging tests are imperative. In this context, since biopsy and imaging exams become imperative in its diagnosis and surgical planning, we describe a case report where an inverted papilloma (IP) mimicked an esthesioneuroblastoma (olfactory neuroblastoma) (ENB) in radiological images, aiming to contribute to the differential diagnosis of these two conditions. Case report: A 69-year-old woman complained of nasal obstruction, frontal headache and left-sided proptosis with the rhinoscopy revealing an expansive lesion in the ipsilateral nasal fossa. Computed tomography (CT) and magnetic resonance imaging (MRI) reviewed a solidocystic dumbbell lesion involving the anterior and left nasal fossae, centered on the cribriform plate and associated with intracranial peripheral cysts, a classic ENB findings. The patient underwent left frontoethmoidectomy with excision of the nasal tumor, but the biopsy, however, revealed an IP. Conclusion: We present a case report of a PI in which imaging on CT and MRI simulated an ENB, likely representing an atypical manifestation of a rare disease. It is hoped that, in light of the above, this work will aid in the differential diagnosis of both conditions.